An improved model for metal-hydrogen storage tanks – Part 1: Model development. (9th February 2016) - Mohammadshahi, Shahrzad S.; Gould, Tim; Gray, Evan MacA.; Webb, Colin J.
Abstract: The complexity of the metal-hydrogen interaction and the critical role of thermal management in a metal-hydride storage tank necessitate comprehensive mathematical modelling before a suitable design can be chosen and subsequently implemented. Existing models have been analysed and integrated into an enhanced model which incorporates several features more suited to practical applications using an intermetallic metal-hydride tank. These include matching initial conditions of the model to physically achievable experimental conditions, the ability to vary the cooling system fluid temperature and realistic modelling of hydrogen injection and extraction from the tank as well as incorporating the non-ideal gas equation and modifying the equilibrium pressure and effective thermal conducting equation based on experimental data. Highlights: Improved multiphysics model for hydrogen storage MH tank applications. Model of hydrogen injection at start of absorption cycle. Model of hydrogen release during desorption cycle. Use of fitted experimental data for effective thermal conductivity and equilibrium pressure. Variable thermal management temperatures.